The aerodrome an exhibition dedicated to the memory of Michael Stanley - Watkins, Jonathan 1957- (Ikon, 2019)
This catalogue is dedicated to the memory and curatorial achievements of Michael Stanley, who tragically died in 2012. Co-curated with David Austen and George Shaw and structured loosely on Rex Warner's 1941 wartime novel 'The Aerodrome', a book that made a great impression on Stanley, it includes many of the artists he worked with, all of whom held him in great affection and regarded him as one of their own. Jenny Saville, for example, whose first solo show in a British public gallery took place at MAO in the year of his death, describes Stanley as someone who wasn't scared of history or of being radical. He was as likely to be enthusing about working with a sculptor in his nineties, [as] raising funds to facilitate a young filmmakers vision. His poetic sensibility, combined with a can-do attitude where everything's possible, is what made him so magnetic and convincing. It includes an introduction co-written by Modern Art Oxford Director, Paul Hobson and Ikon Director Jonathan Watkins, as well as texts by artists George Shaw, David Austen and Carrie Stanley. The catalogue also features biographies on all artists showing in the exhibition. Exhibition: Ikon Gallery, Birmingham, UK (12.06.-08.09.2019)
Impressum: Ikon Gallery, Birmingham, 12 June - 8 September 2019. - The exhibition catalogue is co-published by Ikon Gallery, Birmingham and Modern Art Oxford
Keywords: Stanley, Michael -- 1975-2012; Warner, Rex -- 1905-1986 -- The Aerodrome; Geschichte 2004-2019; Geschichte 2000-2019; Rezeption; Umkreis; Kunst; Künstler; Großbritannien; Ausstellungskatalog -- Ikon Gallery -- 12.06.2019-08.09.2019 -- Birmingham; Bildband